2021
DOI: 10.1038/s41467-021-25267-2
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent kinetic pathways of heterogeneous ice nucleation competing between classical and non-classical nucleation

Abstract: Ice nucleation on the surface plays a vital role in diverse areas, ranging from physics and cryobiology to atmospheric science. Compared to ice nucleation in the bulk, the water-surface interactions present in heterogeneous ice nucleation complicate the nucleation process, making heterogeneous ice nucleation less comprehended, especially the relationship between the kinetics and the structures of the critical ice nucleus. Here we combine Markov State Models and transition path theory to elucidate the ensemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 95 publications
(136 reference statements)
0
23
0
Order By: Relevance
“…90 For heterogeneous nucleation of ice, Markov state MD modelling suggests that the relative rates of classical and two-step nucleation can depend on temperature, with a transition point above which classical mechanism is predicted to dominate. 91…”
Section: Diversity and Evolving Theory: Beyond Classical Nucleationmentioning
confidence: 99%
“…90 For heterogeneous nucleation of ice, Markov state MD modelling suggests that the relative rates of classical and two-step nucleation can depend on temperature, with a transition point above which classical mechanism is predicted to dominate. 91…”
Section: Diversity and Evolving Theory: Beyond Classical Nucleationmentioning
confidence: 99%
“…As shown in Figure S3, the free-energy profiles of ice nucleation on the chessboard-like surface with different sizes contain only one barrier, indicating that the nucleation process follows the picture of classical nucleation theory. Li et al , reported that on the hydrophilic wurtzite-structured surfaces the first water layer can form rhombic and hexagonal ice patches. The ice nucleation on these wurtzite-structured surfaces adopts complex pathways with the coexistence of classical and nonclassical nucleation pathways.…”
Section: Resultsmentioning
confidence: 99%
“…This capability of forming a 3-D structure depends on the configuration of the first monolayer. When water molecules in the first monolayer have dangling OHs pointing away (Figure a), developing a 3-D network is possible because the dangling OHs can form interlayer hydrogen bonds to connect to the second monolayer of water . Then, from the second layer of water, the third layer can develop, and so forth.…”
Section: Working Mechanisms Of Nanoreactorsmentioning
confidence: 99%
“…When water molecules in the first monolayer have dangling OHs pointing away (Figure 11a), developing a 3-D network is possible because the dangling OHs can form interlayer hydrogen bonds to connect to the second monolayer of water. 80 Then, from the second layer of water, the third layer can develop, and so forth. In this case, the solid surface is playing a seeding role in the creation of a 3-D structure of water such as the nucleation of gas hydrates and ice.…”
Section: Working Mechanisms Of Nanoreactorsmentioning
confidence: 99%
See 1 more Smart Citation